Gellan gum capped silver nanoparticle dispersions and hydrogels: cytotoxicity and in vitro diffusion studies - Dhar, Sheetal; Murawala, Priyanka; Shiras, A.; Pokharkar, V.; Bhagavatula L. V. Prasad (Nanoscale, 2012)
The preparation of highly stable water dispersions of silver nanoparticles using the naturally available gellan gum as a reducing and capping agent is reported. Further, exploiting the gel formation characteristic of gellan gum silver nanoparticle incorporated gels have also been prepared. The optical properties, morphology, zeta potential and long-term stability of the synthesized silver nanoparticles were investigated. The superior stability of the gellan gum-silver nanoparticle dispersions against pH variation and electrolyte addition is revealed. Finally, we studied the cytotoxicity of AgNP dispersions in mouse embryonic fibroblast cells (NIH3T3) and also evaluated the in vitro diffusion of AgNP dispersions/gels across rat skin.